SELF EFFICACY REMAJA PANTI ASUHAN DAN PENINGKATANNYA MELALUI PENDEKATAN BIMBINGAN KELOMPOK - Atieka, Nurul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2015)
Abstract: One aspect that affects the independence and confidence teens orphanage to live in the wider environment, and ready to tackle the problems in the struggle for life in the future is self-efficacy. The purpose of this study is to describe and improve the efficacy of adolescent orphanage by providing group counseling. Type of research is experimental. The study population is adolescent orphanage upper secondary school age with the number 120. These samples included 51 adolescents orphanage for the control group and 14 adolescents orphanage for the experiment. Group selection of samples using proportional random sampling technique. The research instrument that is the scale of self-efficacy, and data analysis techniques with a t-test. Results of the study are the level of self-efficacy orphanage teenagers are in the low category of being. Group counseling services performed may increase self-efficacy, it is evident from the increase in the average score, and through statistical analysis known that that greater than t 2,897 (2,000), and the significance value 0.005> 0.05. Thus, the group counseling services significantly affect the increase in a self-efficacy teenage orphanage.Keywords: self-efficacy, group counseling, teens